2017
DOI: 10.1371/journal.pone.0177928
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA signatures as "liquid biopsies" for interrogating hepatotoxic mechanisms and liver pathogenesis in human

Abstract: MicroRNAs (miRNAs) released into the peripheral circulation upon cellular injury have shown a promise as a new class of tissue-specific biomarkers. We were first to demonstrate that next-generation sequencing analysis of serum from human subjects with acetaminophen-induced liver injury revealed a specific signature of circulating miRNAs. We consequently hypothesized that different types of hepatic liver impairments might feature distinct signatures of circulating miRNAs and that this approach might be useful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…To determine whether acetaminophen overdose might increase PD risk, the levels of circulating miRNAs in serum from both patients with PD and subjects who were hospitalized with acetaminophen overdose were compared ( Table ). Serum levels of three circulating miRNAs, hsa‐miR‐192, hsa‐miR‐24, and hsa‐miR‐30c, showed the same directional change (increase or decrease when compared with healthy subjects) in patients with PD and in subjects with acetaminophen overdose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether acetaminophen overdose might increase PD risk, the levels of circulating miRNAs in serum from both patients with PD and subjects who were hospitalized with acetaminophen overdose were compared ( Table ). Serum levels of three circulating miRNAs, hsa‐miR‐192, hsa‐miR‐24, and hsa‐miR‐30c, showed the same directional change (increase or decrease when compared with healthy subjects) in patients with PD and in subjects with acetaminophen overdose.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating miRNAs were found to be stable even under conditions as harsh as boiling, extreme pH, long‐time storage at room temperature, and multiple freeze‐thaw cycles . Details regarding sample collection, sample preparation, sequencing, and data processing can be found in Krauskopf et al ., and see for patient characteristics and levels of liver damage markers. Circulating miRNAs characteristically present in the serum of patients with PD were gathered from Khoo et al .…”
Section: Methodsmentioning
confidence: 99%
“…24 Krauskopf et al also used RNA sequencing and reported substantially increased circulating isomiRs with DILI in humans. 25 In mice, Chowdhary et al performed Northern blotting to demonstrate miR--122 isomiRs in the circulation following paracetamol toxicity. 26 In our study, the concentration of isomiRs increased with sample degradation and, importantly, microRNA degradation was substantially increased with DILI.…”
Section: Uloq (Concentration Cv) 1578mentioning
confidence: 99%
“…42,43 With RNA-sequencing technologies allowing for cheaper and efficient analyses of the full panel of miRNAs, rather than a targeted qPCR assay, researchers have started to employ miRNA profiles or "liquid biopsy" approaches in the patients with tissue injury, as well as in disease populations. 37,[43][44][45] These approaches not only help identify additional miRNA candidates but also provide a pattern of miRNAs associated with both certain disease states and types of injury.…”
Section: Translation Of Mirnas To the Clinicmentioning
confidence: 99%